Acute Type B Aortic Dissection Present as Innominate Vein Compression Syndrome: A Rare Presentation - Chuan-Lei Chao; Chung-Lieh Hung (International Journal of Gerontology, 2016)
The term “innominate (brachiocephalic) vein compression syndrome” was first coined by Wurtz et al in 1989 to describe a patient who presented with “unilateral superior vena cava syndrome.” Here we report a 70-year-old male with comorbidities including hypertension, end-stage renal disease with a left arm arteriovenous fistula for hemodialysis, who presented with left brachiocephalic (innominate) vein compression by a Stanford Type B aortic dissection presenting with left arm edema. The diagnosis was confirmed by venography and computed tomography scan, and he underwent successful endovascular stent grafting.